Beyond privacy... intentionality: a look at Abib’s discussions about subjectivity in radical behaviorism - Pompermaier, Henrique Mesquisa (Perspectivas em Análise do Comportamento, 2023)
In this work I present and discuss arguments and problematizations of three texts in which Prof. J.A.D. Abib examines possibilities and limits of the comprehension of subjectivity from a radical behaviorist perspective. With particular attention to the transcription of a communication on the XVIII. Annual Meeting of the Society of Psychology of Ribeirão Preto, I highlight the premises presented by Abib that could substantiate a radical behaviorist proposal for the problem of knowledge of subjectivity; and I explore and expand discussions on how compromises with the notions of access and privacy corrupt this opportunity. Considering this frame, I present the author’s challenges about the potential of a critical reexamination of the radical behaviorist proposal from the encounter with the notion of intentionality of consciousness, from existential-phenomenological tradition. Finally, I transcribe the research plan proposed by Abib to explore this possibility of going beyond the limits of the radical behaviorist proposal when considering subjectivity.